Isha Yoga Practices and Participation in Samyama Program are Associated with Reduced HbA1C and Systemic Inflammation, Improved Lipid Profile, and Short-Term and Sustained Improvement in Mental Health: A Prospective Observational Study of Meditators - Sadhasivam, Senthilkumar; Alankar, Suresh; Maturi, Raj; Williams, Amy; Vishnubhotla, Ramana V.; Hariri, Sepideh; Mudigonda, Mayur; Pawale, Dhanashri; Dubbireddi, Sangeeth; Packiasabapathy, Senthil; Castelluccio, Peter; Ram, Chithra; et al. (Frontiers in Psychology, 2021)
Samyama is an 8-day Isha Yoga intensive residential meditation experience requiring several months of extensive preparation and vegan diet. As other forms of meditation have shown benefit for physical and psychological health, we hypothesized that participation in Samyama would offer enhanced physical and psychological benefits. This was an observational study of adults before and after the Isha Samyama retreat, along with non-meditating controls (household significant others). Surveys assessed anxiety, depression, mindfulness, joy, vitality, and resilience through validated psychometric scales at 4 timepoints (T1, baseline; T2, just before Samyama; T3, just after Samyama; T4, 3 months later). Blood biomarkers were assessed including hemoglobin (Hb), HbA1c, lipid profile, and C-reactive protein (CRP). This clinical trial was registered at Clinical Trials.gov (NCT04366544; https://clinicaltrials.gov/ct2/show/NCT04366544). Results: Depression and anxiety scores significantly decreased in Samyama participants from T1 to T3, with the effect most pronounced in those with baseline depression or anxiety. Vitality, resilience, joy, and mindfulness increased in participants from T1 to T3 (sustained at T4), body weight decreased by 3% from T1 to T3, and triglycerides (TG) were lower from T2 to T3. Compared with controls, Samyama participants had lower HbA1c and high-density lipoproteins (HDL) at T2, and lower CRP at all timepoints. Conclusions: Isha Samyama participants had significantly reduced depression and anxiety, and improved well-being for at least 3 months after the retreat. Physical health improved as evidenced by weight loss and lower TG, and improved HbA1C, HDL, and CRP compared with controls. Samyama preparation and retreat are effective in improving physical and mental health. Future studies may examine Samyama as an alternative non-pharmacological therapy in patients with clinical depression and/or anxiety.